1998
DOI: 10.1007/s003740050397
|View full text |Cite
|
Sign up to set email alerts
|

Soil enzyme activities in the rhizosphere of field-grown sugar beet inoculated with the biocontrol agent Pseudomonas fluorescens F113

Abstract: Abstract. Pseudomonas fluorescens F113, which produces the antimicrobial compound 2,4-diacetylphloroglucinol is a prospective biocontrol agent. Soil enzyme activities were used to investigate the ecological impact of strain F113 in the rhizosphere of field-grown sugar beet. There were distinct trends in rhizosphere enzyme activities in relation to soil chemistry (studied by electro-ultrafiltration). The activities of enzymes from the phosphorus cycle (acid phosphatase, alkaline phosphatase and phosphodiesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…According to the results obtained showed that the isolates belonged to the genus Bacillus [28,29]. Soil enzyme assays have been used to investigate biochemical processes such as soil organic matter formation and degradation, nutrient cycling and interaction between inoculants and indigenous microbial population in soils and is a possible integrative measure of soil quality to reflect biological status of soils [4,30]. Fluorescein diacetate activity was considered in the present study as it was reported to be a better biological indicator of soils than dehydrogenase activity [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results obtained showed that the isolates belonged to the genus Bacillus [28,29]. Soil enzyme assays have been used to investigate biochemical processes such as soil organic matter formation and degradation, nutrient cycling and interaction between inoculants and indigenous microbial population in soils and is a possible integrative measure of soil quality to reflect biological status of soils [4,30]. Fluorescein diacetate activity was considered in the present study as it was reported to be a better biological indicator of soils than dehydrogenase activity [31].…”
Section: Resultsmentioning
confidence: 99%
“…Plants and microorganisms together increase P availability by solubilising inorganic P and mineralizing organic P. These include beneficial rooting characteristics, mycorrhizae, fungi, bacteria, root exudates and production of phosphatase enzymes. Enzyme activities have been proposed as a tool to monitor changes in soil nutrient cycling resulting from the interaction between inoculants and indigenous microbial population [4]. They found perturbation in soil enzyme activities following the inoculation of Pseudomonas fluorescens in the rhizosphere of wheat.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was carried out in 1994, near Bandon (County Cork, Ireland), at a site where the ecological impact of F113Rif on ecosystem functioning has been studied using a combination of different approaches (30,31,35). The field site, soil characteristics (brown podzolic soil), and farming conditions have been described in detail elsewhere (30).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the interactions between the Phl-producing inoculant P. fluorescens F113Rif and RCFP appeared essentially to have involved phenomena other than Phl-mediated antagonism (probably microbial competition), and these interactions did not result in a modification of the structure or of the high level of strain diversity of the RCFP community. Despite its impact on RCFP, the inoculant had no effect on key aspects of ecosystem functioning (30,31,35). a Commercial antibiotics were also tested.…”
Section: Fig 2 Diversity Of Rapd Profiles For 16 Isolates Randomly mentioning
confidence: 99%
“…To overcome these problems, biological remediation has recently been developed and beneficial agents, such as Bacillus subtilis (Shinji Mizumoto et al, 2007;Wang J et al, 2007;Marc Ongena et al, 2005),and Pseudomonas flurescens (ZHANG et al, 2007; D.C. Naseby et al, 2001Naseby et al, , 1998 are widely used.…”
Section: Introductionmentioning
confidence: 99%